2017
DOI: 10.20944/preprints201706.0100.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating climate change and land use impacts to explore forest conservation policy

Abstract: A scenario-based approach to the impacts of land use and climate change can help in identifying future policy directions. This study models the impacts of different land use and climate change scenarios on the forest ecosystems of South Korea to identify national-scale forest policy options. Climatically suitable forest areas for 1,031 climate vulnerable plant species were identified for current time and for 2050. We calculated change in species richness under four climate projections. We built forest conversi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our study also found high species richness of rarity classes and of nationally listed endangered and endemic species in each rarity class in these mountains (Figure and Figure ), which indicates our simple approach can identify high biodiversity areas for rare species. We suggest that further field surveys in these areas could help identify high priority plant conservation areas, that biological monitoring focused on tracking populations of narrow geographic range plant species be implemented in the northeastern parts of South Korea, and that regional urban development and land use plans should consider the preservation of the high biodiversity in this area (Choe & Thorne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found high species richness of rarity classes and of nationally listed endangered and endemic species in each rarity class in these mountains (Figure and Figure ), which indicates our simple approach can identify high biodiversity areas for rare species. We suggest that further field surveys in these areas could help identify high priority plant conservation areas, that biological monitoring focused on tracking populations of narrow geographic range plant species be implemented in the northeastern parts of South Korea, and that regional urban development and land use plans should consider the preservation of the high biodiversity in this area (Choe & Thorne, ).…”
Section: Discussionmentioning
confidence: 99%